DERIVAÇÃO DE UMA ESCALA DE TEMPO DE DESCORRELAÇÃO LAGRANGIANA PARA UMA CAMADA LIMITE ESTÁVEL - Virnei Silva Moreira (Ciência e Natura, 2013)
In the present study a new formulation for the lagrangian decorrelation time scale in the stable boundary layer (CBL) is proposed. This new model is compared with a well-known relation proposed by Sorbjan(1989).